Strategi Guru dalam Membentuk Karakter Disiplin dan Peduli Lingkungan Kepada Siswa Kelas II SDI Nurul Huda - Dilla Nita Ongki Samsinta; Anang Hadi Cahyono; Ach Andriyanto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study seeks to elucidate the tactics employed by educators in cultivating discipline and environmental consciousness among second-grade pupils at SDI Nurul Huda. Character education plays a crucial role in forming pupils' personality, encompassing principles such as discipline and environmental consciousness. This research employs a qualitative methodology utilizing a case study technique. Data collecting methodologies encompass observation, interviews, and documenting. The study's findings reveal that educators employ several tactics, including habit building, modeling, class responsibility roster scheduling, and motivating visual media, to impart these character characteristics. Moreover, students' active involvement in cleaning initiatives and the upkeep of the school environment contributes significantly to the cultivation of an environmentally conscious character. These findings are anticipated to enhance character education approaches in primary schools.